What are the priority research questions for digital agriculture?. (March 2022) - Ingram, Julie; Maye, Damian; Bailye, Clive; Barnes, Andrew; Bear, Christopher; Bell, Matthew; Cutress, David; Davies, Lynfa; de Boon, Auvikki; Dinnie, Liz; Gairdner, Julian; Hafferty, Caitlin; et al.
Abstract: There is a need to identify key existing and emerging issues relevant to digitalisation in agricultural production that would benefit from a stronger evidence base and help steer policy formulation. To address this, a prioritisation exercise was undertaken to identify priority research questions concerning digital agriculture in the UK, but with a view to also informing international contexts. The prioritisation exercise uses an established and effective participatory methodology for capturing and ordering a wide range of views. The method involves identifying a large number of participants and eliciting an initial long list of research questions which is reduced and refined in subsequent voting stages to select the top priorities by theme. Participants were selected using purposive sampling and snowballing to represent a number of sectors, organisations, companies and disciplines across the UK. They were each invited to submit up to 10 questions according to certain criteria, and this resulted in 195 questions from a range of 40 participants (largely from England with some representation from Scotland and Wales). Preliminary analysis and clustering of these questions through iterative analysis identified seven themes as follows: data governance; data management; enabling use of data and technologies; understanding benefits and uptake of data and technologies; optimising data and technologies for performance; impacts of digital agriculture; and new collaborative arrangements. Subsequent stages of voting, using an online ranking exercise and a participant workshop for in-depth discussion, refined the questions to a total of 27 priority research questions categorised into 15 gold, 7 silver and 5 bronze, across the 7 themes. The questions significantly enrich and extend previous clustering and agenda setting using literature sources, and provide a range of new perspectives. The analysis highlights the interconnectedness of themes and questions, and proposes two nexus for future research: the different dimensions of value, and the social and institutional arrangements to support digitalisation in agriculture. These emphasise the importance of interdisciplinarity and transdisciplinarity, and the need to tackle the binary nature of current analytical frames. These new insights are equally relevant to contexts outside the UK. This paper highlights the need for research actions to inform policy, not only instrumentally by strengthening the evidence base, but also conceptually, to prompt new thinking. To our knowledge this methodology has not been previously applied to this topic. Graphical Abstract: ga1 Highlights: Policy on digital agriculture requires a stronger evidence base. A prioritisation exercise was conducted in UK to identify priority research questions. 195 questions from a range of participants were clustered into seven themes. 27 priority questions (15 gold, 7 silver and 5 bronze) were identified. The questions provide a research framework to steer policy, both in UK and beyond.